PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAIN PADA PEMBELAJARAN SEJARAH KELAS X DI SMA NEGERI TUGUMULYO - Nurul Pratiwi; Ira Miyarni Sustianingsih; Yeni Asmara (Jurnal Binagogik, 2024)
This research aims to implement the Student Facilitator And Explain learning model significantly and thoroughly so that it can improve learning outcomes in student history learning in class X at Tugumulyo State High School. Researchers use research with quantitative methods and use quasi-experiments. The research population used the entire class Sampling uses Simple Random Sampling. Based on the results of the research and discussion, it can be concluded that the history learning outcomes of class This is in accordance with the post-test t-test value at the significance level ᵅ = 5% obtained t = 3.66 t table = 1.697. The average student history learning result after implementing the Student Facilitator And Explain learning model was 69.50 and the percentage of students who had achieved learning completion reached 100%.